An integrative framework of technology acceptance model and personalisation in mobile commerce. (28th August 2006) - Hsu, H.Y. Sonya; Kulviwat, Songpol
Personalisation has emerged as a key strategy to unlocking the customer's loyalty in mobile service businesses. The objective of the article is to examine customer satisfaction and delight derived from using personalised applications and services in the context of mobile commerce. Results from the survey indicate the amount of generalised messages that customers receive has no effect on either customer satisfaction or customer delight. Further, the preference of multimedia messages and the perceived usefulness of personalised message could increase customer satisfaction, but not customer delight. However, only text messages could make customers satisfied and at the same time could increase customer delight. Implications and avenues for future research are discussed.